UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI MAHONI (Swietenia mahagoni) TERHADAP Shigella dysenteriae - Asiska Permata Dewi; Annisa Fauzana (LPPM Universitas Abdurrab, 2017)
One of the plants that can be used as traditional medicine is mahogany (Sweitenia mahagoni). The presence of flavonoid compounds in mahogany seeds is suspected as a compound that serves to inhibit bacterial growth. One of the antibacterial effects is to treat diarrhea diseases caused by Shigella dysenteriae. Diarrhea is infectious intestinal disease a public health problem in developing countries. The aim of this research is to know and measure the inhibition zone of ethanol extract of mahogany seed to the growth of Shigella dysenteriae bacteria with concentration 25%, 50%, 75%, 100%. This research is a descriptive study in vitro using disc method. The result of the research has found that the average inhibition zone diameter at 25%, 50%, 75%, 100% concentration is 6mm, 8mm, 8.33mm, 10.33mm. Negative controls do not provide inhibition and positive control yields an average diameter of 21.33 mm. Based on the above results, it can be concluded mahogany seed extract provides resistance to Shigella dysenteriae.